ANALYSIS OF LANGUAGE STYLES USED BY ANIES BASWEDAN IN POLITICAL CAMPAIGN OF 2024 PRESIDENTIAL ELECTION - Rosmita Ambarita; Rahmat Huda; Anggina Syahrina Daulay; Devita Sari Harahap; Hema Paulina Siregar; Wulan Suci Rahmadani (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Language style is one of the most dynamic and context-dependent aspects of human communication. This research explores the stylistic variation of Anies Baswedan’s speech in two different contexts: his motivational talk to university students and his formal address in the Political Campaign of presidential election.. Using Martin Joos’s (1967) theory of language style, this study identifies how Anies adapts his speech to fit audience, purpose, and setting. The research employs a qualitative descriptive method under a sociolinguistic framework, analyzing the linguistic forms, tone, and communicative intent within both speeches. Findings reveal that Anies Baswedan employs consultative and casual styles when interacting with students, emphasizing warmth, humor, and critical engagement; whereas formal and frozen styles dominate his presidential debate performance, reflecting professionalism, authority, and ideological appeal. This variation highlights Anies’s rhetorical awareness and flexibility in adjusting linguistic strategies to social contexts.